2022
DOI: 10.1108/jeee-07-2021-0269
|View full text |Cite
|
Sign up to set email alerts
|

Changing role of finance in rural small enterprise growth in Ghana

Abstract: Purpose This study aims to build on the emerging understanding that small enterprise growth results from a confluence of different factors. This study seeks to provide additional insights into the nature of these factors and how they influence the growth process of small businesses in rural communities in Ghana. Design/methodology/approach This study undertook a qualitative investigation of 28 small enterprises in three Ghanaian rural districts. Interviews were conducted with owners of the businesses. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Skill training is vital for entrepreneurial expertise needed in small business startups, while business and management education imparts essential managerial competence for daily and corporate decisions (Goodrich et al, 2018). Consequently, training has positively influenced women's entrepreneurship performance in various countries, including Ghana, Nigeria, the USA, Tanzania, and Canada (Kuada, 2022).…”
Section: Empirical Review On Micro-training/skill Development and Wom...mentioning
confidence: 99%
“…Skill training is vital for entrepreneurial expertise needed in small business startups, while business and management education imparts essential managerial competence for daily and corporate decisions (Goodrich et al, 2018). Consequently, training has positively influenced women's entrepreneurship performance in various countries, including Ghana, Nigeria, the USA, Tanzania, and Canada (Kuada, 2022).…”
Section: Empirical Review On Micro-training/skill Development and Wom...mentioning
confidence: 99%
“…To address this gap, this paper throws light on the ways that women navigate around the problem of limited access to formal credit facilities in order to start, operate and expand their enterprises as well as the factors that shape their attitudes towards different credit sources. The study focuses on the micro-sector since most female-owned businesses in the sub-Saharan Africa context are micro-enterprises, and the micro-enterprise sector is critical to the livelihoods of women and their dependents (Kuada, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most development economists agree that a viable solution to the unemployment problem in Africa and other developing nations is private small enterprise development and youth entrepreneurship. This suggestion is based on the understanding that as the number of small private enterprises grow, the number of job opportunities will increase (especially for the youth), and the overall wealth of nations will also increase (Kuada, 2022b). Unfortunately, past studies have shown that unavailability of financial resources is a key constraint to the growth of small enterprises in Africa (Quartey et al, 2017;Asongu and Nwachukwu, 2018).…”
Section: Introductionmentioning
confidence: 99%